Fintech adoption drivers for innovation for SMEs in Indonesia - Deni Pandu Nugraha; Budi Setiawan; Robert Jeyakumar Nathan; Maria Fekete-Farkas (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The rapid evolution of technology and a large number of smartphone users are transforming the way the masses access financial services. Fintech companies consistently innovate in developing customized products and services for users and SMEs to increase financial access and inclusiveness to achieve the Indonesian national financial inclusion target of 90 percent by 2024. Access to digital financial products via Fintech contributes to greater financial inclusion for SMEs, particularly during the COVID-19 pandemic, which restricted economic activities. Using an extended TAM model, this study explores the driving factors of Fintech adoption for Indonesian SMEs during the COVID-19 outbreak. Data analysis of 415 respondents was conducted utilizing Smart-PLS 3.0 software. The findings confirm perceived usefulness, perceived ease of use, government support, trust, and user innovativeness to have a direct positive effect on the intention of SMEs to adopt Fintech. The result also reveals that financial literacy indirectly correlates with Fintech adoption mediated by user innovativeness. This indicates that Fintech could contribute to bridging financial inclusion where SMEs with lower financial literacy can utilize financial products and services via Fintech. This is a positive contribution of Fintech for SMEs in developing economies. The present study suggests that policymakers could foster the expansion of Fintech business infrastructure to improve access to SME financial services.
Keywords: 650; digitization in finance; extended TAM; Indonesian SMEs; SME Innovativeness; Sustainable Development Goals 10